Treating tuberculosis with high doses of anti-TB drugs: mechanisms and outcomes - Yuhui Xu; Jianan Wu; Sha Liao; Zhaogang Sun (BMC, 2017)
Abstract Tuberculosis (TB) is considered as one of the most serious threats to public health in many parts of the world. The threat is even more severe in the developing countries where there is a lack of advanced medical amenities and contemporary anti-TB drugs. In such situations, dosage optimization of existing medication regimens seems to be the only viable option. Therapeutic drug monitoring study results suggest that high-dose treatment regimens can compensate the low serum concentration of anti-TB drugs and shorten the therapy duration. The article presents a critical review on the possible changes that occur in the host and the pathogen upon the administration of standard and high-dose regimens. Some of the most common factors that are responsible for low anti-TB drug concentrations in the serum are differences in hosts' body weight, metabolic processing of the drug, malabsorption and/or drug-drug interaction. Furthermore, failure to reach the cavitary pulmonary and extrapulmonary tissues also contributes to the therapeutic inefficiency of the drugs. In such conditions, administration of higher doses can help in compensating the pathogenic outcomes of enhancement of the pathogen's physical barriers, efflux pumps and genetic mutations. The present article also presents a summary of the recorded treatment outcomes of clinical trials that were conducted to test the efficacy of administration of high dose of anti-tuberculosis drugs. This review will help physicians across the globe to understand the underlying pathophysiological changes (including side effects) that dictate the clinical outcomes in patients administered with standard and/or high dose anti-TB drugs.